2023
DOI: 10.1021/acs.macromol.3c00981
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Poly(methyl methacrylate) with Different Sulfur-Containing End Groups on Gold Nanoparticles and Their Interfacial Assembly into Superlattice Films

Abstract: Grafting polymer ligands on gold nanoparticles (AuNPs) by gold−sulfur (Au−S) bond is a facile way commonly employed to fabricate gold−polymer hybrid NPs (AuNP@ polymer). By using the reversible addition−fragmentation chain transfer (RAFT) radical polymerization, it is convenient to present sulfur-containing end groups to polymer ligands, such as dithioester and trithioester groups, which can be usually transferred to thiol/thiolactone/ disulfide groups by aminolysis reaction. However, these groups show differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…However, when the concentration exceeded a certain range, such as 200 mg mL −1 , a multilayered structure was formed due to the excessive number of NPs and the drastically increased viscosity. In addition, the spreading of the NP dispersion is also related to the grafting density of polymer ligands, which was recently confirmed by Liu et al 114 It was found that a minimum grafting density of 0.51 chains per nm 2 is needed for the effective spreading of ordered self-assembled NPs into large-area 2D NP superlattices. The influence of grafting density on the superlattice structure was recently studied by Kim and coworkers.…”
Section: Preparation Of 2d Np Superlattices By Evaporation-induced In...mentioning
confidence: 63%
See 1 more Smart Citation
“…However, when the concentration exceeded a certain range, such as 200 mg mL −1 , a multilayered structure was formed due to the excessive number of NPs and the drastically increased viscosity. In addition, the spreading of the NP dispersion is also related to the grafting density of polymer ligands, which was recently confirmed by Liu et al 114 It was found that a minimum grafting density of 0.51 chains per nm 2 is needed for the effective spreading of ordered self-assembled NPs into large-area 2D NP superlattices. The influence of grafting density on the superlattice structure was recently studied by Kim and coworkers.…”
Section: Preparation Of 2d Np Superlattices By Evaporation-induced In...mentioning
confidence: 63%
“…The interparticle distance is basically dependent on the grafting density and chain length of the polymer ligands. As presented by Liu et al , 114 the interparticle distance is positively related to the grafting density. However, as mentioned above, when the grafting density is not sufficient, it is difficult to obtain large-area 2D NP superlattices.…”
Section: Preparation Of 2d Np Superlattices By Evaporation-induced In...mentioning
confidence: 65%
“…In a single modification, the heterocyclic carbonyl undergoes chemo- and regioselective amidation, while in the additional presence of a Michael acceptor (e.g., maleimide), a double modification takes place (ring opening, followed by a thiol–X reaction). , The unique reactivity of TLs can be introduced through the commercially available homocysteine thiolactone (HCTL), which can be easily modified through the amine in the α-position (Figure ). Hence, it has been extensively used for postpolymerization modifications, toward sequence-defined and functional polymers, surfaces, , hydrogels, , and bioconjugate materials. …”
Section: Introductionmentioning
confidence: 99%
“…13,14 The unique reactivity of TLs can be introduced through the commercially available homocysteine thiolactone (HCTL), which can be easily modified through the amine in the αposition (Figure 1). Hence, it has been extensively used for postpolymerization modifications, 15−17 toward sequence-defined and functional polymers, 18−20 surfaces, 21,22 hydrogels, 23,24 and bioconjugate materials. 25−27 In one of our previous studies, we demonstrated how selected amino acids and the dipeptide carnosine could be attached to a TL derivative, forming polypeptides/polyelectrolytes in a facile one-pot procedure.…”
Section: ■ Introductionmentioning
confidence: 99%